2020
DOI: 10.1093/molbev/msaa090
|View full text |Cite
|
Sign up to set email alerts
|

Extraordinary Sequence Diversity and Promiscuity of Centromeric Satellites in the Legume Tribe Fabeae

Abstract: Satellite repeats are major sequence constituents of centromeres in many plant and animal species. Within a species, a single family of satellite sequences typically occupies centromeres of all chromosomes and is absent from other parts of the genome. Due to their common origin, sequence similarities exist among the centromere-specific satellites in related species. Here, we report a remarkably different pattern of centromere evolution in the plant tribe Fabeae, which includes genera Pisum, Lathyrus, Vicia, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
69
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(75 citation statements)
references
References 80 publications
(141 reference statements)
5
69
1
Order By: Relevance
“…These results together with our bioinformatics analysis of AcCen1K suggest that: (1) AcCen1K does not form long tandem arrays which is supported by the linear shape of RepeatExplorer cluster (Supplementary Figure 1), almost absence of discordantly mapped reads ( Figure 3B) and absence of FISH signals on A. cepa chromosomes and (2) based on the detection of the AfCen1K-FISH signals on four A. cepa chromosomes (Figure 2A) it can be speculated that true high-copy A. cepa centromeric has similarity to AfCen1K-specific region. Our results are in line with reports from other plant species demonstrating a high divergence of CTR sequences between closely related species or even between chromosomes of one species (Jiang et al, 2003;Gong et al, 2012;Melters et al, 2013;Comai et al, 2017;Su et al, 2019;Robledillo et al, 2020;Talbert and Henikoff, 2020). To the best of our knowledge the monomer size of AfCen1K is one of the largest among CENH3 associated CTR known to date.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…These results together with our bioinformatics analysis of AcCen1K suggest that: (1) AcCen1K does not form long tandem arrays which is supported by the linear shape of RepeatExplorer cluster (Supplementary Figure 1), almost absence of discordantly mapped reads ( Figure 3B) and absence of FISH signals on A. cepa chromosomes and (2) based on the detection of the AfCen1K-FISH signals on four A. cepa chromosomes (Figure 2A) it can be speculated that true high-copy A. cepa centromeric has similarity to AfCen1K-specific region. Our results are in line with reports from other plant species demonstrating a high divergence of CTR sequences between closely related species or even between chromosomes of one species (Jiang et al, 2003;Gong et al, 2012;Melters et al, 2013;Comai et al, 2017;Su et al, 2019;Robledillo et al, 2020;Talbert and Henikoff, 2020). To the best of our knowledge the monomer size of AfCen1K is one of the largest among CENH3 associated CTR known to date.…”
Section: Discussionsupporting
confidence: 92%
“…The monomer size for most known CTRs shows a highly phased distribution with a peak around 150-180 bp corresponding to one wrap of the nucleosome (Melters et al, 2013;Yang et al, 2018). However, large CTRs monomers were previously characterized in Solanaceae (Gong et al, 2012), maize (Sharma et al, 2013), and Fabeae (Robledillo et al, 2018;Robledillo et al, 2020) species. Recent large-scale analysis of CENH3-associated CTRs in Fabeae indicated that 9 of 15 studied species have at least one CTR with monomer size >1,000 bp (Robledillo et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations